Greenland Blocking Index 1851–2015: a regional climate change signal. (2nd May 2016) - Hanna, Edward; Cropper, Thomas E.; Hall, Richard J.; Cappelen, John
ABSTRACT: We present an extended monthly and seasonal Greenland Blocking Index (GBI) from January 1851 to December 2015, which more than doubles the length of the existing published GBI series. We achieve this by homogenizing the Twentieth Century Reanalysis version 2c‐based GBI and splicing it with the NCEP/NCAR Reanalysis‐based GBI. For the whole time period, there are significant decreases in GBI in autumn, October and November, and no significant monthly, seasonal or annual increases. More recently, since 1981 there are significant GBI increases in all seasons and annually, with the strongest monthly increases in July and August. A recent clustering of high GBI values is evident in summer, when 7 of the top 11 values in the last 165 years – including the two latest years 2014 and 2015 – occurred since 2007. Also, 2010 is the highest GBI year in the annual, spring, winter and December series but 2011 is the record low GBI value in the spring and April series. Moreover, since 1851 there have been significant increases in GBI variability in May and especially December. December has also shown a significant clustering of extreme high and low GBI values since 2001, mirroring a similar, recently identified phenomenon in the December North Atlantic Oscillation index, suggesting a related driving mechanism. We discuss changes in hemispheric circulation that are associated with high compared with low GBI conditions. Our GBI time series should be useful for climatologists and other scientists interested in aspects and impacts of Arctic variability and change.